2009
DOI: 10.1002/syn.20676
|View full text |Cite
|
Sign up to set email alerts
|

In vivo measurement of somatodendritic release of dopamine in the ventral tegmental area

Abstract: The ventral tegmental area (VTA), the locus of mesolimbic dopamine cell bodies, contains dopamine. Experiments in brain slices have demonstrated that VTA dopamine can be released by local electrical stimulation. Measurements with both push-pull cannula and microdialysis in intact animals have also obtained evidence for releasable dopamine. Here we demonstrate that dopamine release in the VTA can be evoked by remote stimulations of the medial forebrain bundle (MFB) in the anesthetized rat. In initial experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 53 publications
4
28
1
Order By: Relevance
“…While the second substrate overlaps with the voltammograms for 5‐HT, it does not interfere with the concentration of 5‐HT obtained at 0.65 V because its electrolysis peaks occur later in the cyclic voltammogram. We have previously found somatodendritic dopamine release in the ventral tegmental area upon MFB stimulation (Kita et al. 2009), however, because of the low levels of dopamine in the SNR (Heeringa and Abercrombie 1995) and the low sensitivity of the 5‐HT specific waveform to dopamine (Hashemi et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the second substrate overlaps with the voltammograms for 5‐HT, it does not interfere with the concentration of 5‐HT obtained at 0.65 V because its electrolysis peaks occur later in the cyclic voltammogram. We have previously found somatodendritic dopamine release in the ventral tegmental area upon MFB stimulation (Kita et al. 2009), however, because of the low levels of dopamine in the SNR (Heeringa and Abercrombie 1995) and the low sensitivity of the 5‐HT specific waveform to dopamine (Hashemi et al.…”
Section: Discussionmentioning
confidence: 99%
“…1986) that is located in the medial forebrain bundle (MFB). We previously showed that electrical stimulation of the MFB released an unidentified substance in the red nucleus of the rat that we suspected was 5‐HT (Kita et al. 2009).…”
mentioning
confidence: 92%
“…Vesicular monoamine transporter 2 (VMAT2)-positive vesicles, which would underlie Ca 2+ -dependent vesicular DA release from the somoatodendritic area (Rice et al, 1997, Chen and Rice, 2001, Kita et al, 2009), have also been detected in DA neuron dendrites (Nirenberg et al, 1996). Released DA exerts feedback inhibition of DA neuron activity via activation of D2 autoreceptors, causing GIRK-mediated hyperpolarization (Groves et al, 1975, Lacey et al, 1987).…”
Section: - Influences Of Neurotransmitter Inputs On Dopamine Neuronmentioning
confidence: 99%
“…Vesicular monoamine transporter 2 (VMAT2)-positive vesicles, which would underlie Ca 2+ -dependent vesicular DA release from the somoatodendritic area (Chen and Rice, 2001; Kita et al ., 2009; Rice et al ., 1997), have also been detected in DA neuron dendrites (Nirenberg et al ., 1996). Released DA exerts feedback inhibition of DA neuron activity via activation of D2 autoreceptors causing GIRK-mediated hyperpolarization (Groves et al ., 1975; Lacey et al ., 1987).…”
Section: Intrinsic and Synaptic Mechanisms Controlling Da Neuronmentioning
confidence: 99%